Enhancing Lecturer Competence In Developing Case Method-Based Semester Learning Plans - Laode Muh ZulFardin Syah; Mclean HY; Anwar Wahid; Cita St. Munthakhabah R; Zam’ah (Jurusan Teknik Informatika dan Komputer, 2025)
This study provides an in-depth examination of the implementation and impact of a workshop designed to enhance lecturers' competence in developing innovative Semester Learning Plans (RPS) based on the Project/Case Method. Amidst the demands of the Merdeka Belajar Kampus Merdeka (MBKM) policy, which prioritizes active, student-centered learning, lecturers' ability to design authentic and applicable learning experiences has become a crucial factor in improving the quality of higher education and equipping graduates with relevant skills. The workshop, titled